The effect of the strategy of modeling linguistic processes on reading comprehension and expressive performance among fourth grade literary students (Journal of the College of Basic Education, 2024)
The aim of this research is to determine the impact of the strategy of modeling linguistic processes in reading comprehension and expressive performance among fourth grade students, and to achieve the research goal, the researcher adopted an experimental design with partial control, which is the design of the control group with a dimensional test only . The research sample amounted to (50) female preparatory students (literary faculty), which the researcher chose to be a sample for her research, with (25 ) female students for the experimental group, and (25) female students for the control group, including in ( chronological age calculated in months, academic achievement of parents, language ability test, IQ test). The researcher studied the research sample herself, prepared two Tests, the first to measure reading comprehension included ( 25 ) paragraphs, the researcher made sure of its truthfulness, consistency, extracting the distinctive powers of its paragraphs, the coefficient of difficulty, the effectiveness of incorrect alternatives, was applied remotely to the students of the research sample, and the other to measure expressive performance, included an expressive topic, chosen by experts after presenting a number of expressive topics to them, the students write ( research sample) after the application of the experiment .The experiment lasted a whole semester , and after analyzing the data using the autologous test of two independent samples, the research yielded the following results :1-the students of the experimental group outperformed the students of the control group in the reading comprehension test .2-the students of the experimental group outperformed the students of the control group in the expressive performance test .In light of these two results, the researcher confirmed the effectiveness of the independent variable of this research, which led her to draw a set of conclusions, includingRaising the levels of reading comprehension and expressive performance is possible if effective teaching methods and systematic teaching methods are available, and it is also concluded that there is a relationship between a high level of reading comprehension and proficiency in expressive performance, as improvement in reading and understanding ultimately leads to improvement in expression .In light of this, the researcher recommended a number of recommendations, including :Adopting the independent variable of this research, paying attention to teaching strategies that contribute to developing reading comprehension and expressive performance, holding training courses for male and female Arabic language teachers, and not hesitating in applying modern strategies . The researcher suggested: Conduct a study similar to this research in the other stages, conduct a study similar to this research according to the gender variable, and conduct a budget .